Sensitive detection of Mycobacterium bovis in spiked milk using polymerase chain reaction assay - Villanueva, Marvin A; Suzuki, Yasuhiko; nakajima, Chie; Suzuki, Haruka; Fukushima, Yukari; Mingala, Claro Niegos (Archives of Veterinary Science, 2023)
Bovine tuberculosis is a chronic zoonotic disease that affects both animal and human health and imposes serious public health concerns in the world. Intake of non-pasteurized milk is considered the most probable vehicle for the transmission of pathogenic bacteria. In this study, the detection of Mycobacterium bovis BCG in spiked milk using a polymerase chain reaction was performed. The performance of two DNA extraction methods, CTAB/phenol:chloroform:isoamyl alcohol and EXTRAGENMB were also evaluated. In addition, Mycobacterial concentration was tried to determine using the Standard/ Viable Plate Count Method and Spectrophotometric (Turbidimetric) Method. PCR successfully detected M. bovis BCG in spiked milk, detecting approximately up to two bacilli per reaction. The two DNA extraction methods were effective in the isolation of amplifiable DNA, having the advantage of EXTRAGENMB in terms of (1) shorter duration of DNA extraction, (2) less sample manipulation, and (3) ease of execution of the procedure. Quantitative determination of the Mycobacterial population however failed to quantify the bacterial concentration per dilution, suggesting that CFU concentration should be considered an approximation. It is expected that this method can be used for the detection of M. bovis in raw milk samples.